(untitled) (Publicaciones en Ciencias y Tecnología, 2013)
In this work we consider the problem OVO (order value optimization), where m given continuous functions f1; :::; fm, defined on a domain 2 Rn and an integer p 2 f1; :::;mg, the function of order p with p m, is given by f(x) = fip(x)(x), for all x 2 , where ip(x) is a function satisfying fi1(x)(x) fi2(x)(x) ::: fip(x)(x) ::: fim(x)(x): The problem we address is to minimize f with x 2 by a genetic algorithm that by its very nature has the advantage over existing continuous optimization methods, to find global minimizers. We illustrate the application of this algorithm on examples considered showing its efectiveness in solving them.